ICE manual of structural design buildings - Bull, John W. (ICE manuals., 2012)
ICE manual of structural design: buildings is the definitive reference for practising civil and structural engineers involved in the design of buildings. Written and edited by recognised experts from industry and academia, the manual delivers best practice knowledge and practical guidance, covering all key aspects of building design in a single volume. The manual takes a practical, three-part approach to the structural design process {u2013} addressing fundamental principles, concept design and detailed design {u2013} highlighting essential calculations and techniques.